2005
DOI: 10.1210/jc.2004-1356
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic Receptor Polymorphisms and Salbutamol-Stimulated Energy Expenditure

Abstract: The beta-adrenergic system is involved in the control of energy metabolism and expenditure. The beta2-adrenergic receptor (beta2-AR) gene shows polymorphisms that have been associated with obesity in several studies. In vitro and in vivo studies suggest differences in beta2-AR-mediated function between these polymorphisms. The aim of this study was to investigate the influence of genetic variation in codon 16 of the beta2-AR gene on energy metabolism in humans. Thirty-four subjects were recruited [Gly16Gly (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 37 publications
3
20
2
1
Order By: Relevance
“…This investigation extends and clarifies the physiological significance of recent findings that adults with the Arg16Arg variant of the ␤ 2 -AR demonstrate a reduced thermogenic response to selective ␤ 2 -AR activation (iv salbutamol) (25). Because ␤-AR modulation of EE occurs as a result of stimulation of all three ␤-AR subtypes (30,31), our findings are consistent with the concept that this polymorphism likely does not play an important role in determining metabolic responsiveness to endogenous physiological activa- Data are means Ϯ SE.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This investigation extends and clarifies the physiological significance of recent findings that adults with the Arg16Arg variant of the ␤ 2 -AR demonstrate a reduced thermogenic response to selective ␤ 2 -AR activation (iv salbutamol) (25). Because ␤-AR modulation of EE occurs as a result of stimulation of all three ␤-AR subtypes (30,31), our findings are consistent with the concept that this polymorphism likely does not play an important role in determining metabolic responsiveness to endogenous physiological activa- Data are means Ϯ SE.…”
Section: Discussionsupporting
confidence: 84%
“…On the basis of recent observations that the Arg16Arg ␤ 2 -AR polymorphism is associated with reduced sensitivity to selective ␤ 2 -AR stimulation (25), it could have been hypothesized that tonic peripheral sympathetic nervous system activity is greater in adults with that gene variant, causing greater norepinephrine release and agonist-promoted downregulation. Thus an additional novel finding of the present investigation is that genetic variation in codon 16 of the ␤ 2 -AR is not associated with basal MSNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Previous studies have reported associations between codons 16 and 27 polymorphisms and obesity, insulin resistance and hypertension. [12][13][14][15][16][17][18][19][20][21][22] Finally, the substitution of isoleucine for threonine at codon 164 (Thr164Ile), in the receptor transmembrane-spanning domains, alters agonist binding and decreases coupling of the G s protein to the receptor. 23,24 There is evidence from in vitro studies that some of these receptor variants might be important for catecholamine-induced adipocyte lipolysis in humans.…”
Section: Introductionmentioning
confidence: 99%